Atenolol is not effective in reducing ventricular arrhythmia severity on exercise stress test in patients with catecholaminergic polymorphic ventricular tachycardia. (25th November 2020) - Peltenburg, P; Lieve, K.V.V; Van Der Werf, C; Wilde, A.A.M; Brugada, R; Till, J; Ackerman, M.J; Probst, V; Haugaa, K; Swan, H; Kammeraad, J.A.E; Horie, M; et al.
Abstract: : Patients with catecholaminergic polymorphic ventricular tachycardia (CPVT) are at risk for malignant ventricular arrhythmias during exercise and emotions which may lead to sudden cardiac death. Beta-blockers (BB) are the mainstay of therapy in patients with CPVT, but studies comparing the efficacy of different types of BB are scarce. Our objective was to determine the efficacy of different types of BB in reducing the ventricular arrhythmia (VA) severity on exercise stress test (EST) in patients with CPVT. Data was derived from the International CPVT Registry, a large retrospective cohort study. We included patients who had an EST before (pre-EST) and after start of BB (post-EST). We divided the cohort into five groups based on the first prescribed BB and compared pre-EST and post-EST. We included 428 patients (median age 18.5 [11.7–39.6] years, 240 (56.%) female), 155 (36.2%) probands) of whom 38 (8.9%) used atenolol, 131 (30.6%) bisoprolol, 82 (19.2%) metoprolol, 124 (29.0%) nadolol and 53 (12.4%) propranolol. Sex and history of aborted cardiac arrest were similar in all groups. The age at start of BB differed (p<0, 001): patients using bisoprolol were oldest (35.0 [15.7–35.3]) while patients using propranolol were youngest (12.3 [8.8–24.9]). Median daily BB dose in mg/kg was: 1.0 [0.8–2.3] for atenolol, 0.06 [0.05–0.10] for bisoprolol, 0.9 [0.6–1.5] for metoprolol, 1.1 [0.9–1.6] for nadolol and 1.5 [1.1–2.8] for propranolol. Resting heart rate on pre-EST and post-EST was similar in all groups. Patients using metoprolol had a significantly higher maximum heart rate post-EST compared to nadolol and propranolol (161±18 vs 136±19 and 130±22 bpm, p=0, 002 and p=0, 001, respectively). The VA severity decreased significantly after BB (147 (37.9%) (non-sustained) ventricular tachycardia ((NS)VT) and 120 (30.9%) no or isolated ventricular premature beat (iVPB) pre-EST vs 46 (11.4%) (NS)VT and 184 (45.7%) iVPB post-EST, p<0, 001). Examining the different groups, the VA severity decreased significantly after BB in all but atenolol (13 (40.6%) (NS)VT and 8 (25.0%) iVPB pre-EST vs 9 (25.0%) (NS)VT and 15 (41.7%) iVPB post-EST, p=0, 103). Based on these results we conclude that all beta-blockers except atenolol are effective in reducing the VA severity on EST in patients with CPVT. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): E-Rare Joint Transnational Call for Proposals 2015 "Improving Diagnosis and Treatment of Catecholaminergic Polymorphic Ventricular Tachycardia: Integrating Clinical and Basic Science"